What do parents think about the quality and safety of care provided by hospitals to children and young people with an intellectual disability? A qualitative study using thematic analysis - Natalie Ong; Abbie Lucien; Janet Long; Janelle Weise; Annette Burgess; Merrilyn Walton (Health Expectations)
Abstract Objectives Children with intellectual disability experience patient safety issues resulting in poor care experiences and health outcomes. This study sought to identify patient safety issues that pertain to children aged 0–16 years with intellectual disability admitted to two tertiary state‐wide children's hospitals and a children's palliative care centre; to describe and understand these factors to modify the Australian Patient Safety Education Framework to meet the particular needs for children and young people with intellectual disability. Design, Setting and Participants Parents of children with intellectual disability from two paediatric hospitals and a palliative care unit participated in semi‐structured interviews to elicit their experiences of their child's care in the context of patient safety. Thirteen interviews were conducted with parents from various backgrounds with children with intellectual, developmental and medical diagnoses. Results Eight themes about safety in hospital care for children and young people with intellectual disability emerged from thematic analyses: Safety is not only being safe but feeling safe; Negative dismissive attitudes compromise safety, quality and care experience; Parental roles as safety advocates involve being heard, included and empowered; Need for purposeful and planned communication and care coordination to build trust and improve care; Systems, processes and environments require adjustments to prevent patient safety events; Inequity in care due to lack of resources and skills, Need for training in disability‐specific safety and quality issues and Core staff attributes: Kindness, Patience, Flexibility and Responsiveness. Parents highlighted the dilemma of being dismissed when raising concerns with staff and being required to provide care with little support. Parents also reported a lack of comprehensive care coordination services. They noted limitations within the healthcare system in accommodating reasonable adjustments for a family and child‐centred context. Conclusions The development of an adapted Patient Safety Education Framework for children with intellectual disability should consider ways for staff to transform attitudes and reduce bias which leads to adaptations for safer and better care. In addition, issues that apply to quality and safety for these children can be generalised to all children in the hospital. Patient and Public Contribution Parent advocates in the project advisory team were shown the questions to determine their appropriateness for the interviews.